Model calculations of the contribution of tropospheric SO2 to the stratospheric aerosol layer ... - Nalapalu, Chiranjeevi Srinivasan (Universität Potsdam, 2025)
The stratospheric aerosol layer is an important part of the Earth’s atmosphere. It plays a significant role in the radiative balance of the Earth, in stratospheric chemistry and in geo-engineering. Changes in composition in the aerosol layer after volcanic eruptions have been shown to cause an average global cooling effect. Polar stratospheric clouds formed from sulfate aerosols initiate anthropogenic ozone depletion in the Antarctic region. Sulfate aerosols have also been considered in Stratospheric Aerosols Injection experiments in the aerosol layer to reduce global warming. As one can see, the changes in the composition of this layer can have adverse effects on the Earth’s climate. Various aspects of the stratospheric aerosol layer have been studied but many processes in the aerosol layer are still not fully understood. In this study we specifically focus on the the contribution of tropospheric sulfur dioxide SO2 to the stratospheric aerosol layer. Sulfur aerosols in the aerosol layer originate from ... : Die stratosphärische Aerosolschicht ist ein wichtiger Teil der Erdatmosphäre. Sie spielt eine wichtige Rolle für die Strahlungsbilanz der Erde, für die Chemie der Stratosphäre und für das Geo-Engineering. Es hat sich gezeigt, dass Veränderungen in der Zusammensetzung der Aerosolschicht nach Vulkanausbrüchen eine durchschnittliche globale Abkühlung bewirken. Aus Sulfataerosolen gebildete polare Stratosphärenwolken lösen den anthropogenen Ozonabbau in der Antarktis aus. Sulfataerosole wurden auch bei Experimenten zur Injektion stratosphärischer Aerosole in die Aerosolschicht berücksichtigt, um die globale Erwärmung zu verringern. Wie man sieht, können sich Veränderungen in der Zusammensetzung dieser Schicht nachteilig auf das Klima der Erde auswirken. Verschiedene Aspekte der stratosphärischen Aerosolschicht wurden bereits untersucht, aber viele Prozesse in der Aerosol- schicht sind noch nicht vollständig verstanden. In dieser Studie konzentrieren wir uns speziell auf den Beitrag des troposphär- ischen ...